Analysis of students' mathematical representative ability on dimensional space subject matter in terms of socio mathematical norms - Fadhlurrahman, Muhammad Hilmi; Maarif, Samsul (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of the research is to determine the ability of mathematical representation of students based on the level of socio mathematical norms owned by students. This research uses a descriptive qualitative method. The subjects were six students who had high, medium, and low sociomathematical norm categories. This study used questionnaires, written tests, and interviews as data collection instruments. Rasch model method for questionnaires and written tests as a data analysis technique and in interviews analyzed using data reduction, data collection, and conclusion drawing using MAXQDA. The results of this research are: 1). Students with high sociomathematical norm categories have high mathematical representation abilities and so do students with medium and low sociomathematical norm levels, 2) the characteristics of students' representation abilities tend to have symbolic ability indicators and 3) the characteristics of students' sociomathematical norms in this study tend to mathematical communication indicators.